2022
DOI: 10.3389/ijph.2022.1605225
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Tuberculosis Case Notification and Treatment Outcomes in Eswatini

Abstract: Objectives: We investigated the impact of COVID-19 on tuberculosis (TB) case notification and treatment outcomes in Eswatini.Methods: A comparative retrospective cohort study was conducted using TB data from eight facilities. An interrupted time series analysis, using segmented Poisson regression was done to assess the impact of COVID-19 on TB case notification comparing period before (December 2018-February 2020, n = 1,560) and during the pandemic (March 2020–May 2021, n = 840). Case notification was defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…During this time, measures that were executed to curb the spread of COVID-19 such as banning of public transport and eventually lock down may have interfered with the population health seeking behavior hence a decline in TB diagnoses [ 21 ]. Our findings are similar to a study in Eswatini that found a significant decrease in TB CNR during the COVID-19 pandemic [ 22 ]. The increase in TB CNR in 2021 and subsequently 2022 suggests that the number of people with undiagnosed and untreated TB grew during the intense waves of the COVID-19 pandemic resulting in more community transmission of infection and hence increased numbers of people developing TB [ 2 ].…”
Section: Discussionsupporting
confidence: 92%
“…During this time, measures that were executed to curb the spread of COVID-19 such as banning of public transport and eventually lock down may have interfered with the population health seeking behavior hence a decline in TB diagnoses [ 21 ]. Our findings are similar to a study in Eswatini that found a significant decrease in TB CNR during the COVID-19 pandemic [ 22 ]. The increase in TB CNR in 2021 and subsequently 2022 suggests that the number of people with undiagnosed and untreated TB grew during the intense waves of the COVID-19 pandemic resulting in more community transmission of infection and hence increased numbers of people developing TB [ 2 ].…”
Section: Discussionsupporting
confidence: 92%
“…As evidenced by much fewer case noti cations than anticipated in 2020, the COVID-19 pandemic has seriously disrupted TB services [44]. Comparing data from 2019 to 2020, TB noti cations decreased globally by 21%.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Eswatini shows TB case notifications decreased during the pandemic compared to the period prior. Death rate increased to 21.3% compared to 10.8% and the odds of unfavourable outcomes were higher (aOR 2.91, 95% CI: 2.17–3.89) during the pandemic compared to the period prior [ 18 ].…”
Section: Discussionmentioning
confidence: 99%